2013
DOI: 10.1093/toxsci/kft154
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Solubilization and Cytotoxicity of Indium-Containing Particles In Vitro

Abstract: Indium-containing particles (ICPs) are used extensively in the microelectronics industry. Pulmonary toxicity is observed after inhalation exposure to ICPs; however, the mechanism(s) of pathogenesis is unclear. ICPs are insoluble at physiological pH and are initially engulfed by alveolar macrophages (and likely airway epithelial cells). We hypothesized that uptake of ICPs by macrophages followed by phagolysosomal acidification results in the solubilization of ICPs into cytotoxic indium ions. To address this, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 28 publications
(41 reference statements)
2
36
0
Order By: Relevance
“…It has been reported that incubation at 4°C or addition of cytochalasin D, an inhibitor of actin assembly and polymerization, decreased the microparticle uptake of macrophages [23,24,25]. PEMs were cultured with or without IFN-γ (1 ng/ml) for 12 h, and then they were treated with cytochalasin D (5 µg/ml) for 30 min followed by co-incubation with 5-(and-6)-carboxyfluorescein diacetate succinimidyl ester (CFSE)-labeled chicken red blood cells (cRBCs) for 2 h. Additionally, some PEMs were co-incubated with cRBCs at 4°C in a freezer overnight in the presence or absence of IFN-γ.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that incubation at 4°C or addition of cytochalasin D, an inhibitor of actin assembly and polymerization, decreased the microparticle uptake of macrophages [23,24,25]. PEMs were cultured with or without IFN-γ (1 ng/ml) for 12 h, and then they were treated with cytochalasin D (5 µg/ml) for 30 min followed by co-incubation with 5-(and-6)-carboxyfluorescein diacetate succinimidyl ester (CFSE)-labeled chicken red blood cells (cRBCs) for 2 h. Additionally, some PEMs were co-incubated with cRBCs at 4°C in a freezer overnight in the presence or absence of IFN-γ.…”
Section: Methodsmentioning
confidence: 99%
“…RAW cells were cultured in Dulbecco's modified Eagle's medium (DMEM) with 2 mM L-glutamine, 10% fetal bovine serum (FBS), and 50 mg/ml penicillin/streptomycin (Invitrogen Life Sciences, Grand Island, NY). RAW cells were selected for these studies because of their potential to react with and engulf particles Gwinn et al, 2013). BEAS-2B cells were grown in DMEM F12 with 10% FBS and 50 mg/ml penicillin/streptomycin.…”
Section: Cell Culturementioning
confidence: 99%
“…Ionic indium derived from RAW cells was significantly reduced by treatment with CytoD. These data implicate macrophage uptake and solubilization of InP and UITO via phagolysosomal acidification as requisite for particle-induced cytotoxicity and the release of indium ions (Gwinn et al, 2013).…”
Section: In Vitro Studies On Cellsmentioning
confidence: 68%
“…The rather low solubilization in the macrophage cell line, RAW 264.7, of less than 0.1% within 24 h, and even lower solubilization in the epithelial cell line LA-4 of 0.05% (Gwinn et al, 2013) could be an explanation for the very long elimination halflives of 142/124 weeks calculated in the studies with intratracheal administration of 3 or 6 mg/kg to hamsters (Tanaka et al, 2010(Tanaka et al, , 2015 and other phenomena to be discussed below.…”
Section: Discussionmentioning
confidence: 95%